Measurements of the Z0/γ⁎ cross section and transverse single spin asymmetry in 510 GeV p+p collisions - Abdulhamid, Muhammad Ibrahim; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick (Physics letters, 2024)
The differential cross section for Z0 production, measured as a function of the boson's transverse momentum (pT), provides important constraints on the evolution of the transverse momentum dependent parton distribution functions (TMDs). The transverse single spin asymmetry (TSSA) of the Z0 is sensitive to one of the polarized TMDs, the Sivers function, which is predicted to have the opposite sign in p+p →W/Z+X from that which enters in semi-inclusive deep inelastic scattering. In this Letter, the STAR Collaboration reports the first measurement of the Z0/γ⁎ differential cross section as a function of its pT in p+p collisions at a center-of-mass energy of 510 GeV, together with the Z0/γ⁎ total cross section. We also report the measurement of Z0/γ⁎ TSSA in transversely polarized p+p collisions at 510 GeV.
Im Text sind "0" und "∗" hochgestellt
M.I. Abdulhamid, I.M. Deppner, N. Herrmann, Y.H. Leung, Y. Söhngen [und viele weitere]
Gesehen am 19.03.2025
Online verfügbar 21 May 2024, Version des Artikels 23 May 2024